The Symbolical Meaning of Ratibu Ritual Completeness in the Death Ceremony of the Muna Ethnic Community in Muna Regency - La Yani Konisi; I Ketut Suardika; Aslin aslin (Universitas Halu Oleo, 2023)
Abstract: This study aims to describe and analyze the symbolical meaning of equipments in ratibu tradition of Muna Community in Muna Regency because ratibu tradition is a unique tradition carried out by the community of Muna ethnic. The method used in this research is descriptive qualitative. Data collection is done by observation, interviews, and documentation. The data obtained was then analyzed using the following steps: 1) data reduction, 2) data presentation, and 3) verification. The results of this study showed that the symbolical meaning in the implementation of ratibu ritual in the Muna people community, starting from kalengkano ratibu, poratibu, up to kasongkono ratibu are generally symbols of the human body so that it is arranged in the order of the shape of the human body, namely two combs of ripe plantains which is the symbol of human toes is placed at the bottom of haroa rasul then beside it is placed a lapalapa as a symbol of the human arm, on top of the lapalapa and two combs of ripe plantain arranged plates containing boiled eggs, kasinganga eggs, manu kaowei, manu kasinganga, traditional cakes, and so on which is also a symbol of the human body, and the top of haroa rasul is put white rice mixed with red rice and covered with an omelette as haroa head as the symbol the human head. Keywords: Ratibu, ritual, community, Muna ethnic